The Genesis of Public Health Reform in Toronto, 1869-1890 - MacDougall, Heather (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1982)
Between 1869 and 1890, the episodic arrangements which had characterized pre-Confederation public health work in Toronto slowly gave way to a more organized approach. However, the process of change involved continuous conflict between the supporters of privatism and growth and the advocates of intervention and amelioration. The catalyst for much of the debate was Dr. William Canniff who was Toronto's first, permanent salaried Medical Health Officer. His attempts to control disease and improve the quality of urban life were opposed by growth-oriented aldermen and their constituents but were supported by middle class lay and medical reformers as well as the federal and provincial governments. The interplay of these forces replicated the experiences of British and American public health enthusiasts and prefigured developments in other Canadian cities. But Canniff and his supporters were unable to resolve the dichotomy between public good and private interest and therefore bequeathed this legacy to their twentieth century successors.